Parenting Stress in Parents of Children with Autism Spectrum Symptomatology - (:unkn) unknown (My University, 2014)
Children with developmental disorders commonly display behavioral, emotional, and adaptive problems. Parents raising these children often undergo stress at clinical levels, which can lead to a host of negative consequences for both parent and child. Parents of children with autism spectrum disorder (ASD) report significantly higher stress than parents of children with other disorders. Thus, some aspects of autism may present a unique challenge to parents. ASD symptoms are often present in other developmental disorders, which could significantly increase parenting stress. Additionally, the severity of ASD symptoms within a group of children with ASD can greatly vary. Despite rising prevalence estimates of ASD, research on the relationship between ASD symptomatology and stress is scarce. To help remedy this problem, the present study examines relations between ASD symptom severity and parenting stress in a group of children who display varying levels of autism symptoms. This study represents an expansion on prior research that examined characteristics in preschoolers with autism or developmental delay that contribute to maternal stress. This study examines whether diagnostic classification (`autism' vs. `non-autism') is related to parenting stress and whether autism symptom severity (calculated using the Autism Diagnostic Observation Schedule-2 and a measure of social responsiveness) relates to parenting stress across and within participant groups.
Keywords: Autism Spectrum Disorders; Developmental Disabilities; Parental Distress; Parenting Stress; Social Responsiveness